Ecobrick : Alternatif Pengelolaan Sampah di Desa Sodong Basari Pemalang - Eki Tri Baranti; Ragil Kurniawan, Wahyu; Zaqy Azzuhri, Haikal (Universitas Negeri Semarang, 2025)
This article discusses the use of plastic waste through the ecobrick method in making the Telaga Biru tourist sign in Sodong Basari Village. This is because the village has a waste problem that can pollute the environment. So by introducing and applying ecobricks you can reduce the amount of plastic waste in the village, minimize its impact, and increase public knowledge about processing plastic waste into products that have useful value. The method used in this service is outreach regarding the impact of plastic waste and how to make ecobricks. This activity is carried out with the stages of identifying problems with the surrounding environment before finally finding a solution, coordination with the village and youth organiions, outreach and training to several communities, collecting the necessary materials, making ecobricks which are arranged on an iron frame with the words Telaga Biru. This service activity produces a product in the form of a sign with the name